Relationship marketing: The impact of emotional intelligence and trust on bank performance - Heffernan, Troy; O'Neill, Grant; Travaglione, Tony; Droulers, Marcelle (Emerald Group Publishing Limited, 2008)
Purpose – The two aims of this paper are to explore the development of trust for relationships between staff and customers in the banking sector and to investigate possible links between financial performance of relationship manager and their levels of emotional intelligence (EI) and trust. Design/methodology/approach – An internet survey was undertaken, where respondents were asked to complete an EI test and questions relating to trusting behaviour. These data were integrated with financial performance data supplied by the bank. Exploratory and confirmatory factor analysis and correlation analysis was used to identify links. Findings – Trust was found to be made up of three components: dependability; knowledge; and expectations. Further, there were significant correlations between both trust and EI, when compared to the financial performance of a relationship manager. Research limitations/implications – The methods used by the bank to collect performance data have limited the analysis that could be conducted. Practical implications – Increased awareness by the relationship managers of their own emotions, and how they perceive and act upon the emotions of others, should favourably impact financial performance. Originality/value – This paper is an important initial step in highlighting the significance of EI and trust in the relationship marketing/selling arena.